Microsoft Power BI complete reference bring your data to life with the powerful features of Microsoft Power BI - Knight, Devin (Packt Publishing, 2018)
Design, develop, and master efficient Power BI solutions for impactful business insights Key Features Get to grips with the fundamentals of Microsoft Power BI Combine data from multiple sources, create visuals, and publish reports across platforms Understand Power BI concepts with real-world use cases Book Description Microsoft Power BI Complete Reference Guide gets you started with business intelligence by showing you how to install the Power BI toolset, design effective data models, and build basic dashboards and visualizations that make your data come to life. In this Learning Path, you will learn to create powerful interactive reports by visualizing your data and learn visualization styles, tips and tricks to bring your data to life. You will be able to administer your organization's Power BI environment to create and share dashboards. You will also be able to streamline deployment by implementing security and regular data refreshes.
Description based on online resource; title from title page (Safari, viewed February 18, 2019)
Keywords: Power BI; Business Intelligence; Microsoft Excel (Computer file); Microsoft PowerPivot (Computer file); Business intelligence; Computer programs; Information visualization; Computer programs; Business; Data processing; Visual analytics; Electronic books; Electronic books; local